2018
DOI: 10.1016/j.drugalcdep.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of postural sway components in cannabis users

Abstract: Regular cannabis use is associated with increased postural sway, and this appears to be predominantly due to the trembling component, which is believed to reflect the peripheral nervous system's contribution to the sway signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…In chronic users of cannabis, the cerebellum presents neuroanatomical alterations that impair its ability to execute postural adjustments, resulting in trembling . Results from a study published in 2017 suggest that cannabis users show subtle changes in gait, primarily in open‐chain components of walking gait, but not in balance …”
Section: Discussionmentioning
confidence: 99%
“…In chronic users of cannabis, the cerebellum presents neuroanatomical alterations that impair its ability to execute postural adjustments, resulting in trembling . Results from a study published in 2017 suggest that cannabis users show subtle changes in gait, primarily in open‐chain components of walking gait, but not in balance …”
Section: Discussionmentioning
confidence: 99%
“…9,10 Some decrements in psychomotor performance, particularly divided attention and postural sway (horizontal movement around a person's center of gravity), persist even when cannabis users are not acutely intoxicated. 11,12 Other studies show that frequent users have persisting negative effects on impulsivity 13,14 and executive function. 15 Human neuroimaging research confirms that cannabis users experience deficits in brain activation in motor control regions that persist beyond acute intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…One potential mechanism for this is adverse effects on the cerebellum and basal ganglia, both of which express high levels of CB1 receptors. Prior research (Bolbecker et al, 2018) found that chronic cannabis use in HIV− individuals was associated with increased postural sway in individuals who were not acutely intoxicated. Our results are similar to those of Bidwell et al (2020) who found that balance function was impaired after immediate cannabis use and different from those of Pearson-Dennett et al (2017) who found that the effect of long-term cannabis use was associated with long-lasting changes in open-chain elements of walking gait, but the magnitude of change was not clinically detectable.…”
Section: Discussionmentioning
confidence: 99%